2001
DOI: 10.2134/jeq2001.303846x
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Pesticides onto Quartz, Calcite, Kaolinite, and α‐Alumina

Abstract: The fate of pesticides in aquifers is influenced by the small but not insignificant adsorption of pesticides to mineral surfaces. Batch experiments with five pesticides and four minerals were conducted to quantify the contributions to adsorption from different mineral surfaces and compare adsorption characteristics of selected pesticides. Investigated mineral phases included quartz, calcite, kaolinite, and alpha-alumina. Selected pesticides comprised atrazine (6-chloro-N2-ethyl-N4-isopropyl-1,3,5-triazine-2,4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
111
1
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(122 citation statements)
references
References 46 publications
5
111
1
5
Order By: Relevance
“…[1] Wood charcoal proved to be an effective low-cost adsorbent for the removal of lindane [2] and endosalfan [3] from the water environment. Recent studies on atrazine adsorption on iron oxides, [4] Quartz, Calcite, Kaolinite, and α-alumina [5] showed that only Kaolinite was suitable for the adsorption of atrazine.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Wood charcoal proved to be an effective low-cost adsorbent for the removal of lindane [2] and endosalfan [3] from the water environment. Recent studies on atrazine adsorption on iron oxides, [4] Quartz, Calcite, Kaolinite, and α-alumina [5] showed that only Kaolinite was suitable for the adsorption of atrazine.…”
Section: Introductionmentioning
confidence: 99%
“…However, positive influence of non-crystalline to poorly crystalline Al oxides on acetochlor sorption should be highly questionable due to positive significant relationship between Al o and TOC (Table 3). Unfortunately, there are no studies regarding the adsorption of chloroacetanilides onto Al oxides, but Clausen et al (2001) demonstrated that the uncharged herbicides like isoproturon and atrazine did not adsorb on the Al-surfaces of α-alumina.…”
Section: Resultsmentioning
confidence: 99%
“…Hematita inicialmente apresentou potencial zeta de +20 mV, permanecendo positivamente carregada até a adição inicial de P de 0,16 mM, tornando-se negativa (-20 mV) com a dose de 0,32 mM, alcançando -25 mV na maior dose de P. Gibbsita, inicialmente com potencial de +16 mV, tornou-se negativa (-2,9 mV) com a adição inicial de P de 0,064 mM, alcançando -13 mV na maior dose (1,61 mM). Considerando-se a mesma condição de pH (4,5), os resultados aqui encontrados foram semelhantes aos obtidos por Giaveno et al. 21 O LVdf inicialmente (controle) apresentou potencial zeta de aproximadamente + 13 mV, tornando-se negativo (-4 mV) com a dose inicial de P utilizada (0,08 mM), alcançando -11 mV com a maior dose (2,56 mM) (Figura 1).…”
Section: Figura 1 Efeito Da Vinhaça E Da Concentração Inicial De P Sunclassified
“…As cargas na superfície das partículas dos solos estão relacionadas aos fenômenos de superfície, como a dispersão/floculação, 1,2 capacidade de troca de cátions e de ânions, 3 adsorção de pesticidas 4 e de metais pesados. 5 As cargas do solo podem ser do tipo permanente, quando originadas de substituição isomórfica na formação dos minerais, principalmente da fração argila, ou dependentes do pH do meio (variáveis), 6,7 sendo essas últimas comuns em solos tropicais altamente intemperizados ricos em óxidos de ferro e de alumínio.…”
Section: Introductionunclassified